Industrial conflict and its implications for productivity growth - Naples, Michele I. (American Economic Review, 1981)
The results of a factor analysis support the proposition that there are different dimensions to labor militance, and that they behave differently over time. Further research is needed on the extent to which they are sensitive to changes in unemployment, and the extent to which they can explain the behavior of productivity growth in the post-war period. If economic hard times enable employers to put labor on the defensive, then ceteris paribus productivity growth may accelerate. The critical implication for policymakers is that any effort to restore growth which does not take into account the distributive impact of increasing productivity will have only a limited success. Instead of simply exacerbating existing antagonisms between workers and companies, policymakers need to address the source of the conflict: the effect of increasing productivity on the quality of worklife. 13 references, 1 figure, 2 tables.